Enhancing Early Literacy Development among Young Learners through the Marungko Approach: Implications for Cognitive and Language Acquisition - Leticia N. Aquino, (The Bioscan, 2026)
This study examined the effectiveness of the Marungko Approach in enhancing early literacy development among young learners, with particular emphasis on its implications for cognitive and language acquisition. Employing a quasi-experimental research design supplemented by qualitative methods, the study involved twenty-five (25) Grade 2 pupils enrolled during the Academic Year 2022–2023. A pretest–posttest assessment was utilized to determine changes in learners’ literacy competencies following the implementation of the Marungko Approach as a structured reading intervention. Reading development was evaluated across key linguistic domains, including phonemic awareness, morphology, syntax, semantics, and pragmatics, which are essential components of language acquisition and literacy growth. To support instruction and facilitate meaningful learning experiences, various educational resources such as flashcards, visual aids, videos, and interactive literacy activities were integrated into the intervention process. Findings revealed significant improvements in learners’ reading proficiency, decoding skills, language comprehension, and overall literacy performance following exposure to the Marungko Approach. The results suggest that the approach serves as an effective early literacy intervention that promotes foundational reading development while supporting cognitive and linguistic growth among young learners. The study highlights the potential of the Marungko Approach as a developmentally appropriate instructional strategy for strengthening literacy acquisition in early elementary education and contributing to improved educational outcomes.